Numerical Investigation of PV/T System Cooling Using Nanofluids - Khalid Salih Hamoudah; Saleh Etaig (African Journal of Advanced Pure and Applied Sciences, 2024)
A Photovoltaic/thermal system (PV/T) was devised and implemented to investigate enhancements in thermal and electrical efficiency through the utilization of nanofluids as coolants. The electrical efficiency witnessed a decline due to a notable reduction in the maximum power output of the photovoltaic cell as temperature increased. Consequently, this elongated the payback period of the PV system and potentially shortened the lifespan of the PV cell. To address this issue, an effective cooling technique was employed. The PV/T system incorporated a parallel plate thermal collector directly attached to the backside of the PV module using thermal paste. The cooling mechanism involved the use of (Al2O3–water) nanofluid with varying concentration ratios to mitigate the operating temperature. An elevation head of (Al2O3–water) was employed for passive cooling of the PV module. Numerical evaluation of the PV/T system's performance was conducted for different coolant concentrations, employing a 3D numerical analysis with finite element-based software Ansys. Under the influence of nanofluid at various concentration ratios (1–5%vol) at a constant inlet velocity (0.0001 m/s), the outlet temperature significantly increased to 76.6°C, while the PV cell temperature dropped to 51°C at a concentration ratio of 5%. This resulted in an improvement in the electrical efficiency of the solar panel to 12.69% and an increase in the thermal efficiency to 47.6%. The heat extracted from the PV module by the cooling nanofluid contributed to the overall energy output of the system.